Diaphragmatic Ultrasound Assessment in Subjects With Acute Hypercapnic Respiratory Failure Admitted to the Emergency Department - Cammarota, Gianmaria; Sguazzotti, Ilaria; Zanoni, Marta; Messina, Antonio; Colombo, Davide; Vignazia, Gian Luca; Vetrugno, Luigi; Garofalo, Eugenio; Bruni, Andrea; Navalesi, Paolo; Avanzi, Gian Carlo; Della Corte, Francesco; et al. (Respiratory care, 2019)
Early identification of noninvasive ventilation (NIV) outcome predictors in patients with COPD who are experiencing acute hypercapnic respiratory failure consequent to exacerbation or pneumonia is a critical issue. The primary aim of this study was to investigate the feasibility of performing diaphragmatic ultrasound for excursion, thickness, and thickening fraction in highly dyspneic subjects with COPD admitted to the emergency department for exacerbation or pneumonia, before starting NIV (T0) and after the first (T1) and second hour (T2) of treatment. Secondarily, we determined whether these variables predicted early NIV failure. Adult subjects with COPD admitted to the emergency department for exacerbation or pneumonia requiring NIV were eligible. Right-sided diaphragmatic excursion, bilateral thickness, thickening fraction, and arterial blood gas analyses were performed at T0, T1, and T2. Feasibility was estimated by considering the number of subjects whose diaphragmatic function could be evaluated at each time point. At T2, subjects were classified in 2 subgroups according to early NIV failure, which was defined as the inability to achieve a pH ≥ 7.35; the ability to achieve pH ≥ 7.35 indicated NIV success. Of the 22 subjects enrolled, 21 underwent complete diaphragm ultrasound evaluation (ie, right excursion and bilateral thickness at T0, T1, and T2) for a total of 63 excursion and 126 thickness assessments. At T2, 12 NIV successes and 9 NIV failures were recorded. Diaphragmatic excursion was greater in NIV successes than in NIV failures at T0 (1.92 [1.22-2.54] cm versus 1.00 [0.60-1.41] cm, = .02), at T1 (2.14 [1.76-2.77] cm versus 0.93 [0.82-1.27] cm, = .007), and at T2 (1.99 [1.63-2.54] cm versus 1.20 [0.79-1.41] cm, = .008), respectively. Diaphragmatic thickness and thickening fraction were similar in both groups. In our emergency department setting, diaphragm ultrasound was a feasible and reliable tool to monitor highly dyspneic acute hypercapnic respiratory failure subjects with COPD undergoing NIV. (ClinicalTrials.gov registration NCT03314883.).